Cryopreservation of Venda wightii Rchb.f protocorms - Achuth J Sankar (Department of Plant Biotechnology, College of Agriculture, 2014)
Investigations on cryopreservation of protocorms of Vanda wightii Rchb.f an endangered orchid of Western Ghats was carried out to devise a protocol for long-term conservation of their germplasm. The commonly used techniques encapsulation- dehydration and vitrification methods were compared.